Crystallographic orientation and spatially resolved damage for polycrystalline deformation of a high manganese steel. (March 2022) - Xie, Qingge; Yan, Zhiran; Yu, Dunji; An, Ke; Yan, Xingchen; Yin, Shuo; Gillham, Bobby; Wu, Xiaolong; Yang, Ping; Zhao, Zhengzhi; Wang, Yandong
Abstract: Deformation damage during tension and compression were revealed using in-situ neutron diffraction for a high manganese steel: (1) When the tensile stress is increased, an indication of damage is provided when the 111 and 422 lattice strains along the transverse direction give no more contraction or even expansion. This is because that the replacement of slip or twinning activities by crack propagation induces relaxation, which can outweigh contraction of the damaged slip or twinning planes. (2) For compression and also when the stress amplitude is decreased, the increase of the 111, 220, 311, 422 lattice strain amplitudes along the loading direction indicates damage. This is because micro-cracks can decrease the effective elastic modulus and crack propagation is not favored during compression. The identified damage grains for both cases belong to the same set. Distribution of the damaged grains in fractured samples is similar to that from grains featuring large Taylor factors. The cracks mainly distributed at the transverse surface. It is due to stronger deformation heterogeneity and ratcheting events at the surface rather than in the interior. During tension-compression fatigue loading, grain boundaries and the narrow deformation twins often correspond to different amplitudes of transversal contraction and expansion from those in other surface areas. This may trigger surface flaws as nuclei for cracks. The findings point to the important relations among damage, lattice strains, and plastic activities, as well as damage behavior differences between tension and compression. Graphical abstract: Image, graphical abstract